Non-linear models with panle data - Bo E. Honoré (Centre for Microdata Methods and Practice (cemmap), 2002)
Panel data play an important role in empirical economics. With panel data one can answer questions about microeconomic dynamic behavior that could not be answered with cross sectional data. Panel data techniques are also useful for analyzing cross sectional data with grouping. This paper discusses some issues related to specification estimation of nonlinear models using panel data.
Keywords: C23; 330; panel data; nonlinear models; fixed effects; random effects; Panel; Theorie; Nichtlineares Verfahren